THE INFLUENCE OF WORK MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE AS MEDIATED BY LEADERSHIP STYLE (CASE STUDY OF BCA KCU BALIKPAPAN) - Sukmawati, Siti Nur; Shalahuddin, Shalahuddin; Darmawan, Dedi (Universitas Ichsan Sidenreng Rappang, 2023)
The success of a company really depends on the performance of their employees. If employee performance declines, then company goals cannot be achieved. Therefore, it is necessary to understand the factors that encourage higher employee performance. There are various factors that can influence performance, for example work motivation, work discipline and leadership style. This research uses quantitative research methods with a descriptive approach. The data collection technique was carried out by distributing questions via questionnaire to 100 employees who worked at BCA KCU Balikpapan. The collected data will be analyzed using a multiple regression model test. The results of research in writing this scientific work show that all independent variables have a significant influence on the level of employee performance at BCA KCU Balikpapan.